Identification of Culinary Tourism in Padang City - Yanita, Novi; Nadra, Abdiani Khairat; Wimeina, Yudhytia; Rahmah, Aulia (JURNAL PENDIDIKAN DAN KELUARGA, 2023)
Padang City is renowned for its picturesque landscape, rich cultural heritage, and delectable cuisine. However, its culinary tourism potential has not yet been fully realized, which may result in suboptimal travel experiences for tourists. This study aimed to identify culinary tourism attractions in Padang City. The research methodology employed a mixed-methods approach that incorporated both qualitative and quantitative techniques. Data were gathered through questionnaires, interviews, observations, and documentation analysis. The findings indicate that culinary tourism in Padang City can be categorized into three main types: restaurants, cafés, and street food. Based on the menu offered, restaurants can be further classified into two distinct categories: traditional Minang restaurants and fusion restaurants. Some notable clusters of culinary tourism destinations were concentrated in the Padang Beach Area, GOR H. Agus Salim Area, Old Town Area, Gado-Gado Hill Area, Tangsi Back Area, Earthquake Monument Area, and Pondok Area.